International Students and Crime - Chennamsetti, Prashanti (Journal of International Students, 2016)
Knowledge about crime promotes awareness about the existence of a problem and aids in designing appropriate preventive strategies to tackle the problem. The authors promote this awareness throughout their book International Students and Crime, which investigates the phenomenon of international student crime using qualitative methodology. The authors compare data from the US, UK and Australia, and present 150 international student experiences along with opinions of industry professionals.